Understand the Concept of Nidanarthakara Roga w.s.r. to Obesity (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda is a holistic science of life described many fundamental principles related to the Dosha, Dushya, Srotasa, Vyadhi utpatti and Vyadhi cikitsa etc. Ayurveda furthermore presented many aspects related to the prevention of Vyadhi and avoidance of Nidanas in terms of Nidana parivarjana. Nidana plays a key role in manifestation of any diseases. Sometime disease itself acts as Nidana and plays a key role in the onset of another disease. This concept is undertaken by Acarya Caraka under the title Nidanarthakara roga (a disease itself become causative factor for some other disease). The disease manifest first is termed as primary disease, while disease manifest as consequence of primary disease termed as secondary disease. In the today’s time, it is crucial to know the Nidanarthkaratva of any disease. The presenting era is more challenging for medical sciences on account of emerging of various lifestyle diseases. Obesity is one among them. Unhealthy diet habit, sedentary lifestyles are the various Nidanas for Obesity. Now days obesity is burning issue for society due its critical consequences. Sometime obesity itself act as Nidana for various diseases e.g. hypertension, diabetes mellitus, infertility, heart diseases, some form of malignancies etc. To prevent these consequences, we have thorough knowledge of the obesity and it’s Nidanarthakaratva. Here an attempt made to enlighten the knowledge of Nidanarthakara vyadhi and to elaborate the Nidanarthakaratva of obesity.